Hydroclimatological Analysis of Goynuk Stream Basin (Bingol) - Esen, Fatma (Fırat University, 2021)
In this study, Göynük Stream Basin, one of the important river basins of Bingöl Province, has been determined as the study area. By analyzing hydrological (current) and climatological (temperature, precipitation) data of the basin, the trends and correlations with each other were tried to be explained. For this purpose, hydroclimatological data series covering the 47-year period between 1970-2017 were provided. Three different statistical techniques, homogeneity test, trend test and correlation tests were applied to each of the data series obtained. Linear trend analysis and Mann-Kendal test were used to determine the direction distribution and amount of trends. In addition, Kendall tau and Spearman rho tests were applied to determine the correlations of the variables with each other. According to the results of the analysis, the average temperature values of the Bingöl Meteorology Station for the period between 1970-2017 tend to increase and the total precipitation values tend to decrease. A decreasing trend was observed in the current values of Göynük Stream Çayağzı Station. In addition, while there is a positive and linear relationship between precipitation and current, there is a negative and inverse proportional relationship between temperature-precipitation and temperature-current.

Bu çalışmada, Bingöl İli’nin önemli akarsu havzalarından biri olan Göynük Çayı Havzası çalışma alanı olarak belirlenmiştir. Havzaya ait hidrolojik (akım) ve klimatolojik (sıcaklık, yağış) verilerin analizleri yapılarak eğilimleri ve birbirleriyle olan korelasyonları açıklanmaya çalışılmıştır. Bu amaçla 1970-2017 yılları arasındaki 47 yıllık dönemi kapsayan hidroklimatolojik veri serileri temin edilmiştir. Elde edilen veri serilerinin her birine homojenlik testi, eğilim testi ve korelasyon testleri olmak üzere üç farklı istatistiki teknik uygulanmıştır. Eğilimlerin yönü dağılışı ve miktarının belirlenmesinde lineer trend analizi ile Mann-Kendal testi kullanılmıştır. Ayrıca değişkenlerin birbirleriyle olan korelasyonlarını tespit etmek için Kendall tau ve Spearman rho testleri uygulanmıştır. Analiz sonuçlarına göre Bingöl Meteoroloji İstasyonu’nun 1970-2017 yılları arasındaki döneme ait ortalama sıcaklık değerleri artış, toplam yağış değerleri ise azalış eğilimindedir. Göynük Çayı Çayağzı İstasyonu’na ait akım değerlerinde azalış eğilimi gözlemlenmiştir. Ayrıca yağış ve akım arasında pozitif ve doğrusal bir ilişki varken, sıcaklık-yağış ve sıcaklık-akım arasında negatif yönlü ve ters orantılı bir ilişki mevcuttur.
GÖYNÜK ÇAYI HAVZASI’NIN (BİNGÖL) HİDROKLİMATOLOJİK ANALİZİ